Konsep Mahabah Jalaluddin Rumi dan Relevansinya dengan Pelestarian Lingkungan - Al Fitra Ghulam Waffa Safiro; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the concept of mahabah according to Jalaluddin Rumi and its relevance to environmental preservation. The research method used is a qualitative type through literature study. The results and discussion of this study are that there is a concept of love in society that has experienced a reduction in meaning which makes it so narrow. This is due to the lack of public understanding of the concept of mahabah which is often referred to as "love". Society generally thinks that love is synonymous with attraction to the opposite sex, even though love, according to figures, one of which is Jalaluddin Rumi, love is not only limited to that. This research focuses on how the concept of love in Jalaluddin Rumi's point of view, both regarding the nature and implementation in life, especially the environment. As a result, this article provides an overview of how the concept of love should be in human beings and makes that love a way to love God.